1998
DOI: 10.1074/jbc.273.2.903
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Ala-166 with Cysteine in the High Affinity Rabbit Sodium/Glucose Transporter Alters Transport Kinetics and Allows Methanethiosulfonate Ethylamine to Inhibit Transporter Function

Abstract: An alanine to cysteine mutation at position 166 has been introduced by site-directed mutagenesis into the rabbit sodium/glucose transporter (rSGLT1). When expressed in Xenopus laevis oocytes, this mutant transporter (A166C rSGLT1) demonstrates a significantly lower apparent affinity for ␣-methyl glucoside (␣MG) compared with the wild-type transporter (apparent K m ‫؍‬ 0.8 versus 0.15 mM). Using the two-electrode voltage clamp technique, transient currents have also been measured, and for the mutant transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 19 publications
4
33
0
Order By: Relevance
“…Similarly, MTSEA also reacts with A166C in the absence or the presence of Na ϩ (11). In this regard, alkylation of mutants T156C, K157C, and A166C is similar to that of mutant G527 (TM XIII) of hSGLT1 (6) and the sodium/dicarboxylate cotransporter (15), all of which are also independent of Na ϩ .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Similarly, MTSEA also reacts with A166C in the absence or the presence of Na ϩ (11). In this regard, alkylation of mutants T156C, K157C, and A166C is similar to that of mutant G527 (TM XIII) of hSGLT1 (6) and the sodium/dicarboxylate cotransporter (15), all of which are also independent of Na ϩ .…”
Section: Discussionmentioning
confidence: 69%
“…Wright and coworkers (16) have previously proposed the sugar domain to be established by TM X-XIII in the COOH-terminal half of SGLT1. Their laboratory also demonstrated that reacting Q457C with MTSEA inhibited sugar transport, but the mutant could still bind sugar (11). These results suggest that other residues may be important for binding of sugar.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations